Centring a sideshow: local experiences of the First World War in Africa. Issue 2 (3rd May 2016) - Moyd, Michelle
Abstract: The African campaigns of First World War should be thought of as more than 'sideshows.' Rather, historians should research local, ordinary African experiences of the war in order to better understand African perspectives on the war, and also to generate narratives that can be integrated into more inclusive histories of the global war. This essay suggests several different vantage points which could prove generative for a new historiography of the war in Africa.